SEISMICITY ANALYSIS ON SULAWESI REGION BASED ON a- AND b-VALUES FOR THE PERIOD 1976–2024 - Risky Martin Antosia; Raga Mandala Putra; Rizki Wulandari; Reza Rizki; Asido Saputra Sigalingging; Nugroho Prasetyo (Jurnal Neutrino:Jurnal Fisika dan Aplikasinya, 2026)
Seismicity analysis is an essential approach to understanding earthquake occurrence patterns, seismic activity levels, and the potential for large-magnitude earthquakes. This study aims to analyze seismicity parameters in the Sulawesi region using earthquake data from 1976 to 2024 obtained from the United States Geological Survey (USGS). The parameters examined include a-value and b-value derived from the frequency-magnitude distribution (FMD) curve using the ZMAP software. The results show that seismic activity in Sulawesi is dominated by earthquakes of magnitude 4–5 with depths of less than 100 km. The magnitude of completeness (M_c) is determined as 4.5, with an a-value of 6.39 (equivalent to 4.7 per year) and a b-value of 0.831. Spatial maps indicate that high a-values (4) are concentrated in West and Central Sulawesi, while high b-values (0.55) are also clustered in these regions. These findings highlight that West and Central Sulawesi are characterized by dense seismic activity and heterogeneous crustal stress conditions. This study provides a valuable contribution by complementing seismicity parameter information in Sulawesi, particularly in previously uncovered areas, and serves as a basis for earthquake hazard mitigation efforts.